2012
DOI: 10.1164/rccm.201201-0130oc
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-disordered Breathing and Cancer Mortality

Abstract: Rationale: Sleep-disordered breathing (SDB) has been associated with total and cardiovascular mortality, but an association with cancer mortality has not been studied. Results from in vitro and animal studies suggest that intermittent hypoxia promotes cancer tumor growth. Objectives: The goal of the present study was to examine whether SDB is associated with cancer mortality in a community-based sample. Methods: We used 22-year mortality follow-up data from the Wisconsin Sleep Cohort sample (n ¼ 1,522). SDB wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
156
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 404 publications
(171 citation statements)
references
References 30 publications
9
156
0
6
Order By: Relevance
“…These adverse effects of OSA are important mediators of cardiovascular risk (3,4), even in milder forms of OSA (5)(6)(7)(8). OSA has been independently associated with hypertension (9,10), coronary heart disease, stroke, and cardiovascular mortality (11)(12)(13)(14)(15).…”
Section: Measurements and Main Resultsmentioning
confidence: 99%
“…These adverse effects of OSA are important mediators of cardiovascular risk (3,4), even in milder forms of OSA (5)(6)(7)(8). OSA has been independently associated with hypertension (9,10), coronary heart disease, stroke, and cardiovascular mortality (11)(12)(13)(14)(15).…”
Section: Measurements and Main Resultsmentioning
confidence: 99%
“…In addition, recent studies indicate that sleep apnea, which is a well-established risk factor for cardiovascular mortality, is also linked with increased cancer mortality (44).…”
Section: Sleep Disturbances and Cancermentioning
confidence: 99%
“…Conversely, the study by SASANABE et al [15] reported dyslipidaemia as the third most frequent finding. Finally, population-based studies yielded a prevalence of metabolic syndrome in OSA of between 26% and 35% [29][30][31]. A recent population study reported a 44% prevalence of metabolic syndrome in females with AHI .15 events?h -1 [32].…”
Section: Prevalence Of the Metabolic Syndromementioning
confidence: 99%